Efektivitas Pendamping Desa Dalam Meningkatkan Pemberdayaan Masyarakat Melalui Bumdes Di Desa Pengudang Kecamatan Teluk Sebong Kabupaten Bintan - Natalia Anasthasia Silalahi; Jamhur Poti; Fitri Kurnianingsih (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2023)
The purpose of this study is to determine the effectiveness and constraints of Village Assistant in increasing empowerment through village-owned enterprises in the Village of pengudang. This research uses a qualitative descriptive type approach using 3 indicators of effectiveness, according to Duncan in Dewi Nurmalasari et al (2021), which are Goal Achievement, Integration and Adaptation. The results of research of achieving goals carried out by village assistants have been running according to their goals targeting people who are still lacking in understanding Bumdes, Integration, it is necessary to increase the training socialization process for each member/administrator, Adaptation, village assistants have approached and adjusted to the community especially the Bumdes management and bringing about changes in the field of administrative reporting. Then the obstacle or inhibiting factor is the lack of community participation and commitment, and changes in regulations which are obstacles in the mentoring process. The conclusion in this study is that the presence of village assistants in assisting the government in Pengudang village to increase empowerment through BUMDES can be said to have been effective according to the directions and mandate given by the central government. In the future, socialization is needed.